2018
DOI: 10.20961/joive.v1i1.35764
|View full text |Cite
|
Sign up to set email alerts
|

Comparation Between Project Based Learning Aided “Edmodo” and Conventional Learning for Learning Outcomes of Two Dimentional Animation Techniques (Experimental Eleventh Grade Students of Vocational High School)

Abstract: <p>This research is aimed to find out:  (1) the differences learning outcomes between project based learning aided edmodo model  and conventional learning (2) the effectiveness of using project based learning model to increase learning outcomes of two dimentional animation techniques. This research used quasi experimental with pretest-posttest control group design. The population of this research are students of class XI 1 and XI 3 multimedia program of Vocation High School Batik 2 Surakarta with 70 stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…The research results of (Vania et al, 2018), the use of Edmodo as web-based learning increases student motivation in the learning process. (Hizbullah et al, 2018) concluded that the use of Edmodo in project-based learning is more effective in increasing learning outcomes than conventional learning models. A study conducted by (Listiqowati et al, 2021) discoverd that during the Covid 19 pandemic, the use of the Edmodo application was more effective in improving student learning outcomes in online learning.…”
Section: Based On the Observation Findings At Statementioning
confidence: 99%
“…The research results of (Vania et al, 2018), the use of Edmodo as web-based learning increases student motivation in the learning process. (Hizbullah et al, 2018) concluded that the use of Edmodo in project-based learning is more effective in increasing learning outcomes than conventional learning models. A study conducted by (Listiqowati et al, 2021) discoverd that during the Covid 19 pandemic, the use of the Edmodo application was more effective in improving student learning outcomes in online learning.…”
Section: Based On the Observation Findings At Statementioning
confidence: 99%
“…Sports massage is used to help athletes perform, relieve fatigue and recuperate before and after activities (García-Sillero et al, 2021). Hizbullah et al (2018) found a difference in learning outcomes between PjBL models and traditional learning models for students, indicating that PjBL is more successful than traditional learning models for enhancing animation technique learning outcomes. Because PjBL models can boost students' creative and social skills while they learn, the teacher's involvement is critical in implementing and developing learning models that can boost students' creativity and social skills while they learn, making the learning process more meaningful (Taufiqurrahman et al, 2021).…”
Section: Conceptual or Theoretical Frameworkmentioning
confidence: 99%